Psychological contract, engagement and employee discretionary behaviours Perspectives from Uganda - Kasekende, Francis (International Journal of Productivity and Performance Management, 2017)
The purpose of this paper is to examine the mediation effect of employee engagement on the relationship between employer obligations, employee obligations and state of the psychological contract and employee discretionary behaviours. Design/methodology/approach – The empirical data were collected using self-administered questionnaires with 278 participants from 11 commissions and three agencies in the public service in Uganda. The authors used hierarchical regression analysis to investigate the hypotheses. Findings – The results indicate that employer obligations, employee obligations and state of the psychological contract were positively related to employee discretionary behaviours. In addition, employee engagement was found to be a partial mediator between employee obligations, employer obligations and state of the psychological contract and discretionary behaviours among for both subordinate and supervisory staffs. Originality/value – Since little is known about the process by which public service commissions and agencies in Uganda promote employer obligations, employee obligations and state of the psychological contract on discretionary behaviours, this paper contributes to the literature by examining human resource management practices in a developing country context.
Keywords: Uganda; Engagement; Employees; Psychological contracts; Discretionary behaviours